Assessment of Immune Profiles in Patients With Endometriosis and Associated Patient Outcomes [A88]. (May 2022) - Loret de Mola, J. Ricardo; Osorio, Erika Gonzalez; Groesch, Kathleen; Wilson, Teresa; Delfino, Kristin; Braundmeier-Fleming, Andrea
Abstract : INTRODUCTION: Endometriosis is associated with inflammation. We characterized systemic immune populations in patients with endometriosis and identified associations between immune status and therapies (surgical intervention and/or hormonal therapy, HT) on clinical outcomes. METHODS: Peripheral blood was collected on the day of surgery (DOS) and ∼1-3 weeks post-surgical intervention (PSI) from consented subjects (IRB approval #14-220). Thirty-three cases (surgically confirmed endometriosis) and nine controls underwent laparoscopy with obstetrics and gynecology faculty at Southern Illinois University School of Medicine. Peripheral tolerant regulatory T-cells (Tregs) and inflammatory T-helper 17 (Th17) cells were identified via flow cytometry. Outcomes (recurrence of pain) were assessed through review of electronic health records. Categorical variables were compared by the Fisher exact test; continuous variables were compared with the Student t-test or nonparametric equivalent. Predictors of pain recurrence were assessed using Cox proportional hazards regression analyses. RESULTS: Compared to controls, patients with endometriosis had greater inflammation PSI ( P =0.016). Patients with endometriosis who used HT had reduced inflammation compared to patients without HT (1.280 vs. 2.834, respectively; P =.028). In patients with endometriosis, risk of pain recurrence increased with greater inflammation at DOS ( P =.003). Additionally, reduction of inflammation at PSI did not result in decreased risk of pain recurrence ( P =.034). CONCLUSION: Neither surgical intervention nor HT reduced inflammation alone; yet, when used in conjunction, they reduced inflammation in endometriosis patients. Reduction of inflammation following surgical intervention was not effective at reducing the risk of pain recurrence. Thus, while interventional strategies do affect inflammatory status, inflammatory status does not predict clinical outcomes.